Neurological soft signs (NSS) and cognitive deficits in HIV associated neurocognitive disorder. (September 2020) - Forno, Gonzalo; Henríquez, Fernando; Ceballos, María Elena; Gonzalez, Matías; Schröder, Johannes; Toro, Pablo
Abstract: Neurological soft signs (NSS) are frequently found in severe mental disorders, such as Alzheimer's disease, schizophrenia or HIV associated neurocognitive disorder (HAND) which includes asymptomatic neurocognitive impairment (ANI), mild neurocognitive disorder (MND) and HIV-associated dementia. To characterize NSS in patients with HIV we examined them with respect to neuropsychological deficits typically found in the disorder. 67 HIV + patients without a history of head trauma, opportunistic infections, severe psychiatric disorders or acute confounding comorbidities of the Central nervous system (CNS) were recruited. NSS and neuropsychological deficits were examined on the Heidelberg scale and the Cambridge Neuropsychological Test Automated Battery (CANTAB), respectively. Semantic and phonemic verbal fluency were additionally established. According to NIMH and NINDS criteria, 18 patients were diagnosed with ANI and 21 with MND, 28 showed no cognitive deficits. NSS total scores were significantly correlated with several cognitive domains and NSS subscales. These correlations were confirmed when motor performance was entered as a covariate. According to our findings, NSS in HIV positive patients are significantly correlated with deficits in a broad range of neuropsychological domains. Similar findings were reported in schizophrenia, emphasizing the transdiagnostic character of NSS and supporting NSS examination in screening HIV patients for HAND. Highlights: NSS correlates with a broad range of neuropsychological domains, mainly episodic memory and executive dysfunction. NSS is useful as a screening tool for cognitive deficits in patients with HIV. Our findings underlies the transdiagnostic character of NSS.